2017
DOI: 10.15587/2519-8025.2017.109317
|View full text |Cite
|
Sign up to set email alerts
|

The therapeutic efficacy of 1-[4-(1,1,3,3-tetramethyl butyl) phenoxy]-3-(n-benzyl hexametylenimino)-2-propanol chloride in vivo

Abstract: ТЕРАПЕВТИЧНА ЕФЕКТИВНІСТЬ 1-[4-(1,1,3,3-ТЕТРАМЕТИЛБУТИЛ)ФЕНОКСИ]-3-(N-БЕНЗИЛГЕКСАМЕТИЛЕНІМІНІЙ)-2-ПРОПАНОЛ ХЛОРИДУ IN VIVO © З. С. СувороваМетою дослідження було встановлення терапевтичної ефективності похідного арилаліфатичних амі-носпиртів КВМ-194 Літературний оглядДоцільним є пошук сполук з антифунгальною дією серед похідних арилаліфатичних аміноспиртів, оскільки вони проявляють широкий спектр антимік-робної активності, пригнічують ріст та розмноження як бактерій, так і грибів. Так, виразна антибактеріа-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The studies revealed that active compounds belong to III-VI classes of toxicity and cause practically no local irritations (0.10% and 0.25% solutions) (Korotkii et al, 2015). According to the studies by Suvorova (2017), on the model of generalized infection caused by C. albicans, КВМ-194 (derivative of aryl aliphatic alcohols the compound 1-[4-(1.1.3.3-tetramethylbutyl) phenoxy]-3-(N-benzylhexamethyleneimine)-2-propanol chloride) exerted the most notable effect. In the doses of 0.01 LD 50 and 0.001 LD 50 the compound prevents the death of the infected animals, while mortality in the control accounts for 100%.…”
Section: Discussionmentioning
confidence: 99%
“…The studies revealed that active compounds belong to III-VI classes of toxicity and cause practically no local irritations (0.10% and 0.25% solutions) (Korotkii et al, 2015). According to the studies by Suvorova (2017), on the model of generalized infection caused by C. albicans, КВМ-194 (derivative of aryl aliphatic alcohols the compound 1-[4-(1.1.3.3-tetramethylbutyl) phenoxy]-3-(N-benzylhexamethyleneimine)-2-propanol chloride) exerted the most notable effect. In the doses of 0.01 LD 50 and 0.001 LD 50 the compound prevents the death of the infected animals, while mortality in the control accounts for 100%.…”
Section: Discussionmentioning
confidence: 99%